ANALISIS FAKTOR YANG MEMPENGARUHI INTENSITAS JAM KERJA DAN PENDAPATAN BURUH PEREMPUAN DI PASAR KUMBASARI - Paramartha, I Made Krisna; Pramitha Purwanti, Putu Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 2 (2022): VOL 11 NO 2, FEBRUARI 2022 [405-805], 2022)
An increasingly uncertain economy and increasing basic needs have resulted in the disruption of household economic stability, causing women to be active in the labor market. One of the female workers who work in the informal sector is a female dressmaker at Kumbasari Market. The aims of this study are (1) to analyze the effect of age, education, number of dependents on the intensity of working hours of female workers in Kumbasari Market, (2) analyze the effect of age, education, number of dependents, and intensity of working hours on the income of female workers in Kumbasari Market, and (3) to analyze the indirect effect of age, education, and number of dependents on the income of women workers through the intensity of working hours at Kumbasari Market. The sample in this study amounted to 50 female workers who were determined by the accidental sampling method. The analysis technique used is path analysis. The results showed that (1) age, education and number of dependents had a positive and significant effect on the intensity of working hours of female workers in Kumbasari Market (2) age, education, number of dependents, and intensity of working hours had a positive and significant effect on the income of female workers in the market. Kumbasari (3) the intensity of working hours does not mediate the effect of age on the income of female workers, while the intensity of working hours mediates the effect of education and number of dependents on the income of female workers in Kumbasari Market. Keywords : Age, Education, Number of Dependents, Intensity of Hours Worked, Income